THE IMPORTANCE OF CREATING MULTIMEDIAL ELECTRONIC LEARNING RESOURCES (Academicia Globe: Inderscience Research, 2022)
This article provides information on the importance of creating multimedia e-learning resources. Multimedia e-learning resources help to develop the digital education system.